First report of Choanephora infundibulifera causing blossom blight of teasle gourd in India - ARUP CHATTOPADHYAY and BHOLANATH MANDAL, SIDDHARTHA DAS, SUBRATA DUTTA* (Indian Phytopathology, 2017)
Momordica subangulata Blume subsp. renigera (G. Don) de Wilde is an important vegetable in India. In June 2015, blossom blight symptoms of Momordica subangulata subsp. renigera was first time noticed in the experimental plot of Directorate of Research, Bidhan Chandra Krishi Vishwavidyalaya, Kalyani, West Bengal, India. The disease severity ranged from 10-30% and the disease infestation was also recorded from several other districts of West Bengal, India. The zygomycetous fungi, Choanephora infundibulifera (Currey) sacc. is the main causal organism of blossom blight disease. The temperature 28-30Â°C with high humidity (70-90%) prevalent during the rainy season (June-November) favoured the disease development. This is the first report of blossom blight of Momordica subangulata subsp. renigera caused by Choanephora infundibulifera.